Recovery of Puritanism, 1825–1880 - Chapel, Susan Anne (The University of Edinburgh, 2015)
Between 1825 and 1880, the reputation of sixteenth- and seventeenth-century English Puritanism underwent dramatic changes. From the Restoration of 1660 through to the 1820s, Puritanism was vilified or ignored by most ‘respected’ commentators. However, there was then a significant change in attitudes, and by 1874, the historian Samuel Rawson Gardiner was providing a highly positive view of the Puritans’ role in English history. This thesis considers the questions of how and why historical writers contributed to a ‘recovery’ of Puritanism during this period. In addressing these questions, this thesis undertakes a detailed analysis of what a number of leading Victorian men of letters wrote about the Puritans and Puritanism. Thomas Babington Macaulay and Thomas Carlyle in particular were instrumental in the new, more positive interpretation of Puritanism, and they in turn were influential upon diverse writers, including John Charles Ryle, John Stoughton, James Anthony Froude, and Charles Kingsley – who all presented Puritanism positively in their historical writing, but who often had strikingly different agendas. The thesis argues that this ‘recovery’ of Puritanism was very broad and was reflected in different intellectual frameworks and ideas. These included, but were not restricted to, the Whig political reforms of the second quarter of the century; the idealisation of hero-worship; the justification and celebration of Imperial Britain; the Evangelical movement, both Dissenting and within the Church of England; social conservatism regarding the role of women; the support of literary censorship and ‘plain’ fashion; and discussions of appropriate and effective literary and rhetorical styles. Our writers presented their interpretations through a range of media, from overtly teleological pamphlets and public lectures, to novels and dramatic presentations of events, to more source-based, objective and analytical writing that would be recognized as ‘serious history’ today. Through investigating these different angles, the thesis shows how the discipline of history was developing during the second two quarters of the nineteenth century, and considers how the new historical methodologies and approaches influenced both ‘amateur’ and ‘professional’ historical writers.
Keywords: Puritanism; Macaulay, Thomas Babington; Carlyle, Thomas; historiography